Ekploratory Analysis of Higher Order Thinking Skills (HOTS) on Sociological Learning - Wita, Gusmira; Mursal, Irhas Fansuri (JPGI (Jurnal Penelitian Guru Indonesia), 2023)
Higher order thinking skills is one of the skills needed in the 21st century, but it has not yet been fully implemented in schools including in sociology learning. This study aimed to determine the factors affecting HOTS on sociological learning and the dominant factors affecting HOTS on sociological learning. Data collection in this study used questionnaires (196 students of the Senior high school in Yogyakarta), while data analysis using statistical analysis with Exploratory Factor Analysis (EFA) technique. Based on the research that has been done, it were identified that factor affecting HOTS on sociological learning consist of (1) ability to solve the problem; (2) ability to analize; (3) ability to create; (4) ability ti think inductively; (5) ability to deductively; (6) ability to make decition; (7) ability to evaluate; (8) ability to think critically; and (9) ability to conduct social research. However, the dominant factors affecting HOTS learners was the ability to solve the problem with eigen value 7.442 and variance 25.661%. Thus, the better the ability to solve the problems of a learner then HOTS learners are also getting better.